PACE-1-2 bore hole temperature data 2000-2014 - Peter Jansson (Stockholm University, 2016)
This is a complete record from the PACE (Permafrost and Climate in
Europe) bore hole temperature station on the Tarfala ridge, c.
1650 m a.s.l., nearTarfala Research Station. The data set cover the period from establishment until change of the data logger system in 2014. A second data set is available that contains data collected with the new system. The second data set will be updated annually.
Keywords: Climate Science; 40104 Climate Change Processes; 49999 Earth Sciences not elsewhere classified; Other Earth Sciences; Annan geovetenskap; Climate Science; Klimatvetenskap